TINJAUAN YURIDIS TERHADAP LAYANAN “SHOPPEPAY LATER” SEBAGAI PRODUK PINJAMAN ONLINE DI INDONESIA - Astuti, Ni Putu Winda; Kusuma, Putu Riski Ananda; Dantes, Komang Febrinayanti (Jurnal Ilmu Hukum Sui Generis, 2025)
Technological developments and digitalization have driven significant growth in the e- commerce sector, including in Indonesia. One of the innovations that emerged is the ShoppePay Later payment service, which allows consumers to make purchases with the pay later system. However, this convenience also carries risks, such as misuse by users who do not have a fixed income, debt accumulation, and potential personal data breaches. This research seeks to assess the alignment of the contractual provisions embedded within the ShoppePay Later electronic agreement with the prevailing positive legal framework in Indonesia, specifically referring to the Electronic Information and Transactions Law (UU ITE), as well as to explore the regulatory challenges associated with the implementation of online lending mechanisms. The study employs a normative legal research methodology, commonly referred to as library research, which utilizes an analytical approach focused on statutory interpretation and doctrinal review of pertinent legislation and scholarly sources. The findings indicate that ShoppePay Later has demonstrated adherence to several key legal requirements, including the obligation to disclose comprehensive information as stipulated under Article 9 of UU ITE, and compliance with data protection principles pursuant to POJK No. 10/POJK.05/2022. However, there are still regulatory loopholes, especially related to the minimum age of users and income verification, which can trigger the risk of default. The main challenges in implementing regulations include the potential for debt accumulation (over-indebtedness), lack of specific regulations on paylater, the risk of default, and inuniformity in the billing system. Therefore, it is necessary to strengthen regulations by the Financial Services Authority (OJK) and socialize financial literacy to the public to minimize these risks. The study concludes that while ShoppePay Later provides ease of transactions, legal oversight and protection must be improved to create a safer and more responsible online lending ecosystem.